(3OjhGf GHf MLI GdMehjs - (3GHf MLI GdMehj , CHh HcQ Hf Ydj Hf YHO Gddg GdMehj GdGRQGQj, Jbj GdOjf GHf MLg,J (B837 (3g` s ((3Cejf Hf NjQGddg GdYeQj s)
(3ChdgG (B:s
(3GdMeO ddg Ydi fhGdg gPG OjhGf bGd YaG Gddg Yfg jeOM HgG SjO GdeQSdjf hSeGgG CeGf GdNGFa TOJ Hce GdYTGb deG JQfehG aZfhG, hbO WGH GdebGe hReRe s
(3BNQgG (B:s
(3YPHJ eTGQHg HHGQb egLJj aJeJYhG Hjf GdYPjH, hHGQb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B67s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B77 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B764s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs